2013
DOI: 10.1590/s1516-14392013005000071
|View full text |Cite
|
Sign up to set email alerts
|

In situ polymerized wood polymer composite: effect of additives and nanoclay on the thermal, mechanical properties

Abstract: This study concerns the preparation and characterization of wood polymer nanocomposites based on impregnation of styrene acrylonitrile co-polymer-nanoclay intercalating system in presence of glycidyl methacrylate (GMA), a cross linking agent, and vinyl trichloro silane (VTCS) as additives into Simul (Bombex ceiba, L.), a soft wood. The effect of nanoclay and VTCS on the properties of the resultant wood polymer nanocomposites (WPNC) has been evaluated. FTIR spectroscopy shows the interaction among wood, polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…The addition of nanoclay further increased the tortuous path for diffusion of water. Treatment of wood with the modification of nanoclay and silane coupling agent improving the ASE was reported in a previous study (Devi and Maji 2013).…”
Section: Dimensional Stabilitymentioning
confidence: 84%
See 2 more Smart Citations
“…The addition of nanoclay further increased the tortuous path for diffusion of water. Treatment of wood with the modification of nanoclay and silane coupling agent improving the ASE was reported in a previous study (Devi and Maji 2013).…”
Section: Dimensional Stabilitymentioning
confidence: 84%
“…In other words, wood treated using PF/nanoclay admixture had higher density and WPG, regardless of PF concentration, compared to that of the wood treated without nanoclay. Devi and Maji (2013) reported that the incorporation of nanoclay reduced the mobility of the polymer chains that were intercalated between nanoclay interlayers. Lower mobility might reduce the leaching rate of polymer during curing stage due to its slower movement through the wood structure and thus result in higher polymer retention and WPG after being cured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O ganho percentual de massa dos compósitos foi calculado de acordo com a Equação 1, como previamente mencionado em outros estudos [5,6,15,16] .…”
Section: Ganho Percentual De Massaunclassified
“…Production of wood polymer composites involves the impregnation of solid wood by unsaturated monomers followed by in situ polymerization [6][7][8][9]. This method uses the microstructurally organized wood as a template, and the in situ synthesized polymer is the reinforcement, which results in new materials with physical, biological and mechanical properties better than the untreated wood [4,6].…”
Section: Introductionmentioning
confidence: 99%